Energy Absorption and Deformation Pattern Analysis of Initial Folded Crash Box Subjected to Frontal Test - Choiron, Moch. Agus; Ida, Zumrotul; Purnowidodo, Anindito; Rivai, Ahmad (Journal of Energy, Mechanical, Material and Manufacturing Engineering, 2017)
Crash box design as one of the passive safety components in a vehicle had been developed to enhance energy absorption. Initial fold on the crash box is set to facilitate folding during the crash. The aims of this study is to investigate the initial folded crash box with length to thickness ratio subjected to frontal test. The frontal test is modelled by using finite element analysis. Through computer simulation using 9 models, the obtained result was used to provide the better design of crash box. The variations in this study were length to thickness ratio of crash box with length of tube (L) = 115; 132.5; 150 mm and the thickness of tube (t) = 1.6; 2.0; 2.5 mm. The crash box material was assumed as bilinear isotropic hardening material. The velocity used in the simulations was 7.67 m/s with impact mass of 103 kg. Based on the results, it can be shown that 1st model to 8th model produce deformation pattern as concertina mode and 9th model has diamond mode. The 3rd model has the largest energy absorption with value 18.29 kJ.